Maternal and fetal outcome of pregnancy complicated by convulsions - Fonseca, Michelle; Joshi, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Convulsions in pregnancy pose serious morbidity and mortality to both mother and the fetus. Eclampsia being the most common cause. However, many medical disorders like epilepsy, cerebral malaria, meningitis, metabolic disorders etc can result in convulsions in pregnancy. This study was conducted to determine the prevalence of various aetiologies leading to convulsions and to assess how the various demographic-clinical characteristics affect the maternal as well as fetal outcome in patients with eclampsia as compared to those with convulsions other than eclampsia. Methods: This was an observational study conducted over a period of one and a half year at a tertiary institute in India. A total of 56 patients were studied in this duration. The primary objective was to determine the prevalence of the aetiologies causing convulsion as well as the maternal and fetal outcome of the pregnancy complicated by convulsions. The data regarding age, parity, mode of delivery, gestational age at birth, risk factors was obtained by a predesigned proforma. Results: A total of 56 patients were included in the study after screening 18,840 patients in the hospital. Hence the estimated prevalence of convulsions in pregnancy was 1:336 in this hospital. The most common aetiology noted was Eclampsia (69.6%) followed by epilepsy (16.1%). Others included Cerebral Malaria (3.6%), Hypocalcemia (3.6%), Neurocysticerosis (2%), Hypokalemia (1.8%) and Hypoglycemia (1.8%). Maternal case fatality rate was 3.6%. Total perinatal mortality was 14.2% of which 6 (10.7 %) were still birth. Conclusions: Eclampsia is a major cause of convulsions in pregnancy and considered to be the diagnosis unless proved otherwise. However other causes of convulsions should not be ignored. A thorough evaluation of the patient which lays a major emphasis on a detailed history taking and examination, form the crux of diagnosing the cause of convulsions and can expediate a timely and accurate treatment.